Peningkatan Kesadaran Keselamatan dan Kesehatan Kerja melalui Sosialisasi K3 pada Pekerja Bangunan Sederhana di Kecamatan Jagakarsa, Jakarta Selatan - Muhamad Komarudin; Dasa Aprisandi; Widjajanti, Endang; Fonta Ryfaditia Madjid; Silta aliyah azahra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This activity aims to increase the knowledge and awareness of simple building workers about the importance of Occupational Safety and Health (K3), encourage the use of personal protective equipment and reduce the number of work accidents at the project site. This activity was carried out in one of the residents' houses that was being renovated. The method used was a descriptive approach. This activity targets simple construction workers who do not understand the importance of implementing occupational safety and health when working. Socialization that has been done similarly is mostly done in construction and large companies. Socialization is carried out through an educational approach which includes, discussion and demonstration of the use of personal protective equipment and conducting pre-test and post-test which are used to measure the increase in knowledge, also given knowledge about fire prevention at the work site and how to use a lightweight fire extinguisher. The results of the activity showed an increase in participants' knowledge about occupational safety and health by 90% after the socialization of increasing awareness of occupational safety and health. The use of personal protective equipment for workers increased from 0% to 95% at the work site. Future implementation of similar programs is expected to reach more workers and expand awareness about OHS.